Prevention of Pregnancy Complications in Antiphospholipid Syndrome - Czwalinna, Andreas; Bergmann, Frauke (Hämostaseologie, 2020)
Despite a lot of research on antiphospholipid antibodies (aPL), standardization of test systems, and better definition of its clinical symptoms, the pathomechanism of this acquired autoimmune disease is not yet fully explained. Progress in treatment increased the live birth rate in 70 to 80% of women suffering from obstetric antiphospholipid syndrome (OAPS). However, still 20 to 30% will develop adverse pregnancy outcome. Lack of awareness of this disorder as the cause for pregnancy complications is very harmful to mothers and to their newborns. Complications can be avoided or minimized by proper treatment. The aim of this article is to increase the awareness of gynecologists and medical personal for OAPS.
Keywords: antiphospholipid syndrome; antiphospholipid antibodies; aPL profile; adverse pregnancy outcome; recurrent fetal loss